Implementasi Prinsip-Prinsip Ekonomi Syariah Pada Koperasi Pondok Pesantren Ittihadul Usrati Wal-Jamaah Ddi Lerang-Lerang Kabupaten Pinrang - Sitti Mulyana; Desy Arum Sunarta; Wahyuni (STAI DDI Pinrang, 2024)
Sharia economics emphasizes the importance of balance between worldly and afterlife needs, where every economic activity, including in cooperatives, must be in accordance with Islamic principles. These principles include justice, honesty, responsibility, and freedom from usury, gharar, and maysir. Islam views spiritual and material aspects as an inseparable unity.The sharia cooperative at the IUJ DDI Lerang-Lerang Islamic Boarding School, Pinrang Regency, is a real example of the application of Islamic economics in an educational environment. This cooperative functions as a fair and transparent economic forum, as well as an educational medium for students and the community in applying Islamic values ​​in daily economic activities. Researchers are interested in studying its implementation because of its potential in forming Islamic economic character from an early age.The results of the study show that: 1) The implementation of the principles of Islamic economics in this cooperative has reflected the principles of justice, welfare, and mutual assistance in economic activities, especially in providing business capital to members. 2) Although the cooperative has implemented the principles of Islamic economics.